Integration of Practice Style Teaching with Inclusion: Improving Chest Style Swimming Learning Outcomes - Pebriyandi, Pebriyandi; Mashud, Mashud (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. The study aims to improve student learning outcomes in breaststroke swimming through the integration of practice style teaching with inclusion. Materials and Methods. This study used the Classroom Action Research method of Stephen Kemmis and McTaggart model with phases: preparation, implementation, observation, and reflection. The sample totalled 18 people consisting of 3 female students and 15 male students. Data analysis using Microsoft Excel. Results. Based on the results of data analysis, there is an increase in learning outcomes through two cycles according to the research data. Analysis of cycle I completeness data was 38.9% and cycle II was 72.2%. Conclusion. learning physical education on breaststroke swimming material using the integration of the practice style teaching style with inclusion can improve breaststroke swimming learning outcomes. In addition to improving learning outcomes in breaststroke swimming material, it can also train students’ learning independence, student responsibility and student confidence.